Acute effects of basketball competition on physical performance factors in under-18 female players. [Influencia de la competición sobre los factores de rendimiento físico en jugadoras de baloncesto sub-18]. - José María Izquierdo; Juan Carlos Redondo (Ramón Cantó Alcaraz, 2020)
The aim of this study was to analyse and quantify the acute effects of competition on several performance factors in young female basketball players, between playing positions. To this end, 37 regional league players (17.21 ± 0.44 years) performed various tests to measure the rate of perceived of effort, sprint times and jump capacity immediately pre-match (T1), at half-time (T2) and post-match (T3). Tests included measuring perceived effort (RPE), sprinting for 20 metres based on time across 10 m and 20 m and performance of countermovement jumps (CMJ). For subsequent analysis, the sample was divided into three playing positions: guards (n=11), forwards (n=15) and centres (n=11). Associated with the expected increases of RPE (from 0.3-0.5 to 7.1-7.3), results showed very likely negative effects with performance decreased from T1 to T3 measures in 20 m (3.51% for guards) and in CMJ (13.7% for forwards). We found likely and very likely negative effects between T1 and T2 in all positions but we did not between T2 and T3 in CMJ. These findings highlight the need to individualise fitness training, taking into account the match needs and demands of the different playing positions in order to minimise the effects of match fatigue and accelerate post-match recovery.